Edukasi Pengelolaan Keuangan Dalam Meningkatkan Literasi Perencanaan Keuangan Keluarga Nelayan Desa Mattiro Uleng, Kabupaten Pangkep: Pengabdian - Sahade; Bado, Basri; Pahrul; SH, Khairun Nisa; Adriansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service Activity (PKM) aims to provide intensive education on financial literacy and management, focusing on improving the financial planning of fishing families in Mattiro Uleng Village, Pangkep Regency. This activity was motivated by the fluctuating economic conditions of fishermen, which are influenced by the west wind weather and have an impact on their catch, resulting in uncertain income. Initial surveys show that most fisherwomen in Mattiro Uleng Village still have low levels of financial literacy, tend to be overwhelmed in managing cash flow, and behave consumptively when there is a surplus of income, making them vulnerable to debt and poverty. The PKM implementation method included four stages: problem identification through field surveys, material preparation, interactive training and mentoring implementation, and evaluation using pre-tests and post-tests on 30 participating fisherwomen. The training material focused on priority budgeting, simple cash flow recording, and the importance of emergency savings. The evaluation results showed an average increase in participants' knowledge scores of 45%, confirming that education and mentoring play a significant role in changing their understanding of financial planning. This increase in literacy is expected to become the foundation for financial stability and improved welfare for fishing families in coastal areas.